"How Any Woman Does What They Do Is Beyond Comprehension": Media Representations of Meghan Markle's Maternity. Issue 2 (3rd April 2021) - Orgad, Shani; Baldwin, Kate
Abstract: In 2019–2020, Meghan Markle was one of the most intensely mediated mothers in the anglophone media. This article examines how U.K. and U.S. media representations of Markle negotiate, trouble, challenge, regulate, and reassert the boundaries and meanings of contemporary motherhood. Situating Markle's mediated representations in the context of the increasing visibility and shifting meanings of motherhood in contemporary culture, and particularly in the context of the growing visibility of voices and accounts of "mothering while Black, " we examine the mediation of Markle's maternity in three moments: (1) Prince Harry's announcement of the birth; (2) Markle's public outing with the baby, her later interview for an ITV documentary, and the lawsuit she filed against the British tabloid Mail on Sunday ; and (3) the royal couple's South Africa tour. We conclude by examining a fourth mediated moment—"Megxit"—and highlight the mediation of Markle's maternity as a site that might open up a space for rewriting motherhood, and particularly Black motherhood, however limited that space may be.